Numerical Simulation Analysis of Mechanical Properties on Rock Brittle–Ductility Transformation Under Different Loading Rates - Tian, Zhichao; Tang, Chunan; Yu, Chaoyun; Liu, Yejiao; Chen, Shijiang; Jin, Yun (Frontiers in Earth Science, 2022)
A large number of physical tests and numerical simulations have been carried out to study the effect of confining pressure on rock deformation mechanism, and many meaningful results have been obtained. However, the rock deformation mechanism in the actual mine engineering has always puzzled the academic circle. For example, the occurrence of rockburst is actually a unilateral unloading process of rock mass, which cannot be completed by physical test. Therefore, RFPA3D is used to conduct simulation research on the rock under different confining pressures. The damage constitutive equation of rock was deduced by continuum damage mechanics, and the damage coefficients of different rocks were determined by combining the numerical simulation results of stress and acoustic emission, which verified the correctness of the damage constitutive equation of rock. According to the derived the brittle - ductile damage equation to delayed cumulative damage data fit found that the rock in the brittle phase is almost consistent, and into the extended separation, the longer the ductile phase of the rock, the greater the of the rock . On the contrary, the shorter the ductile stage of the rock, the smaller the of the rock, but carrying capacity is larger. The ductile cumulative damage of rock shows a linear upward trend in the later stage of loading, It shows that the bearing capacity decreases sharply, the stability of rock is damaged, and the ductility damage coefficient increases gradually. In this paper, the analysis of brittle-ductile mechanical properties on rock has a certain guiding significance to the prediction of rock burst in deep mines, that is, the early warning is put forward when the rock mass changes from brittleness to ductility to prevent the occurrence of mine disasters.